Khmer American : identity and moral education in a diasporic community - Smith-Hefner, Nancy Joan (University of California Press, 1999)
Based on long-term research among Cambodians residing in metropolitan Boston, this rich ethnography provides a vivid and moving portrait of the trials and tribulations of Khmer American culture, seen from the perspective of elders attempting to preserve Khmer Buddhism in a deeply unfamiliar world. With particular emphasis on Khmer conceptions of personhood, morality, and sexuality, Nancy J. Smith-Hefner considers how this cultural heritage influences the performance of Khmer children in American schools and, ultimately determines Khmer engagement with American culture.